Effect of structured inquiry-based laboratory on thinking skills among Biology students - Lee, Tze Jiun; Kamarudin, Nurzatulshima; Talib, Othman; Hassan, Aminuddin (National Organization of Science Teachers and Educators, 2018)
This study aimed to investigate thinking skills practical achievement tests between Biology students who perform Structured Inquiry-based laboratory (SIL) and students who do not (TT) (only traditional teaching in classroom). Two groups of co-ed Form 4 Biologystudents (n=64) from two public schools in Kuala Lumpur, Malaysia were selected for the study. Lower-order thinking skills (LOTS) questionnaires about practical were tested in the pre-test and post-test. A curiosity index model (as covariate) which was developed by Ainely (1987) (cited by Fulcher, 2004) was used to investigate levels of the curiosityprior the experiment started due to curiosity might affect the behavior being observed. The Curiosity Index analysis, TT students had higher level of curiosity than SIL students but no significant differences. TT groups also exhibited higher Breadth and Depth levels of curiosity than the SIL, with no significant different shown.The students who were exposed to SIL achieved significant higher LOTS post-test mean score than TT group with a small effect size (partial eta squared) of .16. This paper suggested that students’ thinking skills can to be nurtured with the suitabletypes of instructional method. Eventhough highly curious students tend to explore their surroundings, but without the implementation of proper instructional methods and techniques by their teachers to continuously inspire their curiosity, it is difficult for them to acquire higher level thinking skills.